Nilai-Nilai Sosio Kultural Masyarakat Padang Pariaman - Muhammad Alfi; Dihamri Dihamri; Zairin Zairin (Universitas Prof. Dr. Hazairin, S.H, 2022)
Socio-cultural values have shown a transition period of economic, social, and cultural patterns that are constantly changing and shaping the contours of the future. It denotes a structure of feelings within which a series of cultural practices are continually changing. In addition, there is a growing awareness of the centrality of uncertainty in cultural life. This means a greater understanding of the differences between cultures and the accelerated course of life. In order to keep up with the changing globalization trends, we need to work together based on cultural diversity. The purpose of this study was to identify the sociocultural values that exist in the Padang Pariaman community by using qualitative research methods using a phenomenological approach. The phenomenological approach is used to find out more deeply about the information available to informants. The results of the research that have been obtained are 4 socio-cultural values that exist in the Padang Pariaman community, namely: 1) Objects of Cultural Advancement, 2) Kinship Patterns, 3) Livelihoods and 4) Local Wisdom Values that exist in the Padang Pariaman Community. These socio-cultural values are still attached to the people who live in Padang Pariaman. The use of this value as a guide for brands to live in society and manage the environment.